Life cycle assessment of renewable liquid hydrocarbons, propylene, and polypropylene derived from bio-based waste and residues: Evaluation of climate change impacts and abiotic resource depletion potential. (15th December 2022) - Tähkämö, Leena; Ojanperä, Aarni; Kemppi, Joni; Deviatkin, Ivan
Abstract: Replacing virgin fossil resource use in plastic production with renewable feedstock is largely seen as a feasible solution to avoid the extraction of fossil resources and thus combat climate change and depletion of finite natural resources. This study assesses the climate change impacts and fossil energy resource depletion potential of producing renewable intermediate products, namely renewable liquid hydrocarbons, renewable propylene, and renewable polypropylene that can replace fossil alternatives in plastics production. These products were fully derived from bio-based waste and residue raw materials: used cooking oil, waste and residues from vegetable oil processing, animal fat, and fish fat. All three studied renewable products had lower impacts on climate change and fossil energy resource depletion than their fossil-based alternatives. The partial carbon footprint of renewable polypropylene was −2.24 kg CO2 -eq. and 0.90 kg CO2 -eq. when including and excluding biogenic carbon, respectively. Renewable polypropylene had at least 81% lower carbon footprint and at least 78% lower consumption of fossil fuels when compared to fossil-based polypropylene over their entire life cycle. The benefits of renewable intermediate products, compared to their fossil-based alternatives, were also supported by the sensitivity analysis of the allocation method to the used raw materials. Highlights: Renewable PP made of waste and residues had a carbon footprint of 0.90 kg CO2 -eq. Abiotic depletion potential of fossil fuels (ADPf ) of renewable PP was 14 MJ. Carbon footprint and ADPf of renewable PP were lower compared to fossil PP. The order of performance did not change in the sensitivity analysis.